2014
DOI: 10.1007/s10853-014-8550-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of electronic properties of tin, gallium, and bismuth chalcogenide-filled single-walled carbon nanotubes

Abstract: In the present work, the channels of singlewalled carbon nanotubes (SWCNTs) were filled with tin sulfide (SnS), gallium telluride (GaTe), and bismuth selenide (Bi 2 Se 3 ). The successful encapsulation of the compounds was proven by high-resolution transmission electron microscopy. The electronic properties of the filled SWCNTs were studied by optical absorption spectroscopy, Raman spectroscopy, and X-ray photoelectron spectroscopy. It was found that the embedded metal chalcogenides have different influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…The introduced substances were shown to modify the electronic structure of nanotubes (). Inorganic compounds and nonmetals caused hole doping of SWCNTs , whereas organometallic molecules and metals led to electron doping of tubes. It was found that the host nanotubes protected the encapsulated materials from environmental factors ().…”
Section: Introductionmentioning
confidence: 99%
“…The introduced substances were shown to modify the electronic structure of nanotubes (). Inorganic compounds and nonmetals caused hole doping of SWCNTs , whereas organometallic molecules and metals led to electron doping of tubes. It was found that the host nanotubes protected the encapsulated materials from environmental factors ().…”
Section: Introductionmentioning
confidence: 99%
“…The optical absorption spectroscopy was applied to identify the presence of charge transfer in the SWCNTs filled with FeCl 2 , FeBr 2 , FeI 2 [ 12 ], CoBr 2 [ 13 ], ZnCl 2 , ZnBr 2 , ZnI 2 [ 14 ], AgCl, AgBr, AgI [ 15 ], CdCl 2 , CdBr 2 , CdI 2 [ 16 ], CuCl [ 17 ], CuCl, CuBr, CuI [ 18 ], PrCl 3 [ 19 ], TbCl 3 [ 20 ], GaSe, GaTe [ 21 , 22 ], SnS, SnTe [ 22 , 23 ], Bi 2 Se 3 [ 22 ] and Bi 2 Te 3 [ 24 ]. The optical absorption spectrum of SWCNTs includes several characteristic peaks.…”
Section: Methods Of the Investigation Of The Electronic Properties Of Filled Swcntsmentioning
confidence: 99%
“…Raman spectroscopy was applied to investigate the modified electronic structure of SWCNTs filled with MnCl 2 , MnBr 2 [ 35 , 36 ], FeCl 2 , FeBr 2 , FeI 2 [ 12 ], CoBr 2 [ 13 ], NiCl 2 , NiBr 2 [ 37 ], ZnCl 2 [ 20 ], ZnCl 2 , ZnBr 2 , ZnI 2 [ 14 ], AgCl, AgBr, AgI [ 15 ], AgCl [ 38 , 39 ], CuCl [ 17 ], CuI [ 40 , 41 ], CuCl, CuBr, CuI [ 18 ], CdCl 2 [ 20 , 42 ], CdCl 2 , CdBr 2 , CdI 2 [ 16 ], PbCl 2 , PbBr 2 , PbI 2 [ 43 ], SnF 2 [ 44 ], RbI [ 45 ], RbAg 4 I 5 [ 46 ], TbCl 3 [ 20 , 47 , 48 ], TbBr 3 , TbI 3 [ 48 ], TmCl 3 [ 24 , 47 ], PrCl 3 [ 19 , 47 ], LuCl 3 , LuBr 3 , LuI 3 [ 49 ], HgCl 2 [ 50 ], GaSe, GaTe [ 21 , 22 ], SnS, SnTe [ 22 , 23 ], Bi 2 Se 3 [ 22 ] and Bi 2 Te 3 [ 24 ], Ag […”
Section: Methods Of the Investigation Of The Electronic Properties Of Filled Swcntsmentioning
confidence: 99%
See 1 more Smart Citation
“…The filling of SWCNTs with fullerene C 60 [14] and RuCl 3 [15] was firstly performed in 1998 and since then the topic has attracted increasing attention. SWCNTs were filled with different simple elemental substances, metals [16][17][18][19][20][21][22] and nonmetals [17,23], chemical compounds, metal halogenides [24][25][26][27][28][29], metal chalcogenides [30][31][32][33][34] and metal oxides [35,36] as well as molecules, fullerenes and their derivatives [37][38][39][40][41] and metallocenes [42,43].…”
Section: Introductionmentioning
confidence: 99%